Jogada de letra: um estudo sobre colocações à luz da semântica de frames - Souza, Diego Spader de (Universidade do Vale do Rio dos Sinos, 2015)
The present thesis aims at the discussion of the relation that exists between the linguistic phenomenon of collocations and the concepts of Frame Semantics theory (FILLMORE, 1982; 1985). The study has arisen in the context of two research projects developed by the SemanTec group, Field – Football Expressions Dictionary (CHISHMAN, 2014), already available on the web, and Olympic Modalities Electronic Dictionary (CHISHMAN, 2014), still in early stage. Both dictionaries are organized around the notion of semantic frame proposed by Fillmore (1982; 1985), in such a way that the thesis seeks to demonstrate in which way this concept (and the concepts surrounding it) are related to the lexicographic treatment given to collocations. Thus, the literature review, presented in chapters 2 and 3, discusses the theoretical basis of the studies of collocations and Frame Semantics. The research method consists of the analysis of 74 collocations of football language. The choice of these structures was made after the study of 500 lexical combinations extracted from a Brazilian Portuguese corpus of football discourse through the Sketch Engine software. The analysis of the 74 collocations happens in two steps: the first one is dedicated to investigate the quantitative aspects of the data set and the structural characteristics of football language collocations; the second phase focuses on the relation between these combinations and the theoretical assumptions of Frame Semantics and its computational counterpart, FrameNet, in order to see in which way this theoretical outline treats collocations in lexicographic contexts. Among the main results of the first phase of analysis is the fact that a major part of football collocations are verbal, such as score goal and send the ball, which demonstrates that sport language is marked by the dynamics of actions and events that take place in a game. Besides, it was also possible to realize that nominal collocations are strongly connected to the materials, participants and places of football context. The second phase demonstrated that collocations in the scope of frame-based dictionaries act as lexical units, concept arising from FrameNet. Because they are considered lexical units, collocations are seen as frame evokers, thus characterizing them as terms that must be displayed in the main list of entries. However, it was also possible to note, however, that the frame evoking by collocations many times does not follow the traditional model of FrameNet, especially when it comes to nominal collocations that do not evoke events, but static entities, such as red card and classification table. The present thesis evidences the relevance of Frame Semantics and FrameNet for the study of complex units such as collocations in lexicographic contexts. Another aspect to be mentioned is the importance of the methodological resources of Corpus Linguistics to the area in which this study is included.
Keywords: Colocações; Semântica de frames; FrameNet; Lexicografia computacional; Linguística de corpus; Collocations; Frame semantics; Computational lexicography; Corpus linguistics; ACCNPQ::Lingüística, Letras e Artes::Lingüística